Rationale and design of the African Cardiomyopathy and Myocarditis Registry Program: The IMHOTEP study. (15th June 2021) - Kraus, Sarah M.; Shaboodien, Gasnat; Francis, Veronica; Laing, Nakita; Cirota, Jacqui; Chin, Ashley; Pandie, Shahiemah; Lawrenson, John; Comitis, George A.M.; Fourie, Barend; Zühlke, Liesl; Wonkam, Ambroise; et al.
Abstract: Background: Heart failure (HF), the dominant form of cardiovascular disease in Africans, is mainly due to hypertension, rheumatic heart disease and cardiomyopathy. Cardiomyopathies pose a great challenge because of poor prognosis and high prevalence in low- and middle-income countries (LMICs). Little is known about the etiology and outcome of cardiomyopathy in Africa. Specifically, the role of myocarditis and the genetic causes of cardiomyopathy are largely unidentified in Africans. Method: The Afr i can Cardio m yopat h y and My o cardi t is R e gistry P rogram (the IMHOTEP study) is a pan-African multi-centre, hospital-based cohort study, designed with the primary aim of describing the clinical characteristics, genetic causes, prevalence, management and outcome of cardiomyopathy and myocarditis in children and adults. The secondary aim is to identify barriers to the implementation of evidence-based care and provide a platform for trials and other intervention studies to reduce morbidity and mortality in cardiomyopathy. The registry consists of a prospective cohort of newly diagnosed (i.e., incident) cases and a retrospective (i.e., prevalent) cohort of existing cases from participating centres. Patients with cardiomyopathy and myocarditis will be subjected to a standardized 3-stage diagnostic process. To date, 750 patients have been recruited into the multi-centre pilot phase of the study. Conclusion: The IMHOTEP study will provide comprehensive and novel data on clinical features, genetic causes, prevalence and outcome of African children and adults with all forms of cardiomyopathy and myocarditis in Africa. Based on these findings, appropriate strategies for management and prevention of the cardiomyopathies in LMICs are likely to emerge. Highlights: There are limited data on etiology, treatment and outcome of cardiomyopathy and myocarditis which limits diagnosis, management and prevention. IMHOTEP is a hospital-based study of clinical features, genetics and outcomes of cardiomyopathy in children and adults. IMHOTEP consists of prospectively and retrospectively recruited cases; over 750 participants recruited in the pilot phase. IMHOTEP as a pan-African, multi-centre, single registry that includes all forms of cardiomyopathies. IMHOTEP is a hospital-based investigation and will not address disease burden at the population level.